Statistical assessment of the structure of agricultural activities at enterprises: the effects of zoning - Т. V. Kobylynska (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The article contains results of a statistical assessment of the agricultural output in Ukraine by subsector (plant-growing, animal husbandry) and natural-economic zone (Steppe, Forest- Steppe, Woodlands) for 2016, and its change over 2012–2016. It shows that the largest share of agricultural output is produced by plant-growing subsector (72.7% of the total output), meaning that the Ukrainian agricultural sector is dominated by plant-growing, with a minor significance of animal husbandry. When assessed by natural-economic zone, the structure of agricultural output shows the prevalence of Forest-Steppe zone (with 41.0 percent in the total agricultural area) and ineffectiveness Steppe zone (with 45.3 percent): the agricultural enterprises located in Forest-Steppe zone accounted for 52.0% of the total agricultural output, nearly half of the plant-growing output and 61.2% of the animal husbandry output. An analysis of time series on the agricultural output produced by agricultural enterprises shows the overall positive trend in the agricultural output over 2012–2016, which grew in this period by 28.3%. Part of the assessment are calculations of average agricultural output in 2012–2016, average absolute change in the agricultural output in 2012–2016, average annual ratio of growth in the agricultural output (106.43%) in 2012–2016, the average an- nual rate of growth in the output, produced by agricultural enterprises in Ukraine (6.43%) in 2012–2016.